Optimization in vitro cultivation conditions for an endemic species of Regel's pear - Dyussembekova, D.; Samatova, I.; Bayanbay, S.; Umirzakova, А.; Zhenisbekuly, G.; Kakimzhanova, А. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
The decline in plant diversity is a pressing global issue driven by climate change, plant diseases, and human activities. This reduction in biodiversity poses significant threats to food security and the sustainability of ecosystems. Conserving wild plant species is crucial as they harbor genes that confer resistance to various biotic and abiotic stresses. One such important species is the Regel pear, endemic to Kazakhstan, known for its resistance to drought and diseases. During research efforts, samples of Regel pear were collected from their natural habitats. Using SSR markers, researchers identified samples that exhibited resistance to scab. In a pioneering step, optimal in vitro cultivation conditions were developed to preserve this economically valuable species. The sterilization process for establishing in vitro culture and subsequent regeneration was established. The multiplication conditions were refined using DKW nutrient medium supplemented with 1.0 mg/l BAP, 0.5 mg/l IBA, and 0.2 mg/l GA3. These measures aim to ensure the long-term conservation of genetic diversity and enhance agricultural resilience to environmental changes.
Эндемикалық түр Регель алмұрты үшін in vitro өсіру жағдайларын оңтайландыру
Оптимизация условий культивирования in vitro эндемичного вида груши Регеля
Keywords: Pyrus regelii; invitro culture; endemic; micropropagation